2016
DOI: 10.1016/j.jmr.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Separation of extra- and intracellular metabolites using hyperpolarized 13C diffusion weighted MR

Abstract: This work demonstrates the separation of extra- and intracellular components of glycolytic metabolites with diffusion weighted hyperpolarized 13C magnetic resonance spectroscopy. Using b-values of up to 15,000 s mm−2, a multi-exponential signal response was measured for hyperpolarized [1-13C] pyruvate and lactate. By fitting the fast and slow asymptotes of these curves, their extra- and intracellular weighted diffusion coefficients were determined in cells perfused in a MR compatible bioreactor. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…The increased rate of decay of the lactate signal, which could not be explained by the accelerated decay of the [1‐ 13 C]pyruvate polarization, demonstrated that lactate labeled intracellularly had been released into the extracellular space. The export of hyperpolarized 13 C‐labeled lactate has been observed previously in studies on tumor cells in vitro . Further evidence for the release of labeled lactate in the tumor came from the effects of the inhibition of MCT activity with 4‐CIN.…”
Section: Discussionmentioning
confidence: 91%
“…The increased rate of decay of the lactate signal, which could not be explained by the accelerated decay of the [1‐ 13 C]pyruvate polarization, demonstrated that lactate labeled intracellularly had been released into the extracellular space. The export of hyperpolarized 13 C‐labeled lactate has been observed previously in studies on tumor cells in vitro . Further evidence for the release of labeled lactate in the tumor came from the effects of the inhibition of MCT activity with 4‐CIN.…”
Section: Discussionmentioning
confidence: 91%
“…[78] As a result, diffusion weighted imaging (DWI) can be used to differentiate between intra- and extra-cellular HP metabolites, giving further insight into the metabolic processes and cellular transporters at play.…”
Section: Physical and Biological Properties Of Polarized Agentsmentioning
confidence: 99%
“…Since angiogenesis is a hallmark of cancer, analogous phenomena need to be considered in patient studies . For instance, if a measured AIF is to be extracted for modeling, differential flow suppression between tumor and blood may impact the accuracy of k PL estimation …”
Section: Discussionmentioning
confidence: 99%